The Effect of Product Development on Operational Performance: A Case Study of Ultimate Motors - Musie Ayana Dagnaw; Fitsum Tsegaye Gebreab; Chekol Gizachew Melisew; Hailemichael woldu kiros; Kiflu Chekole Tekle; Mohamad Maulana Ridzki (Journal Of Social Science (JoSS), 2025)
This study entitled “The effect of Product Development on Operational Performance: A Case Study of Ultimate Motors Plc" examines the relationship between product development initiatives and operational performance at Ultimate Motors. The research employed a mixed-methods approach, combining a quantitative survey of 98 employees across product development, manufacturing, and operations functions at Ultimate Motors. The data was collected through an online questionnaire distributed via email and Telegrams. Using Partial Least Squares Structural Equation Modeling, the results indicate that four key product development elements - assembly line, product design, research & development, and product innovation - collectively account for 78.3% of the variance in Ultimate Motors' manufacturing costs and production efficiency. A standout finding is the outsized influence of assembly line optimization, which alone explains 47.7% of the operational performance outcomes. Product design also emerges as a critical factor, contributing 21.6% of the variance. However, the study reveals that inadequate employee training limits the full utilization of advanced design tools. While research & development and product innovation show positive impacts, their relationships with manufacturing costs and production time are not statistically significant. In contrast, effective assembly line management proves to be a crucial lever, driving improved efficiency, reduced costs, and faster timelines. To enhance its operational competitiveness, the study recommends that Ultimate Motors should: adopt advanced CAD software, invest in design team training, leverage CASE tools for innovation, upskill the R&D function, and embrace automation and flexible production technologies.